Fiscal Windfall Curse - Simon Berset; Mark Schelker (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study the impact of a one-off exogenous fiscal windfall on local public finances in the canton of Zurich in Switzerland. The windfall was due to the IPO of Glencore on the London Stock Exchange in 2011. As a result, its CEO paid an extraordinary tax bill of approximately CHF 360 million. About CHF 238 million of that extra tax revenue entered the municipal resource equalization scheme and rained down on the municipalities of the canton of Zurich. This quasi-experimental setup and our unusually rich dataset allow us to estimate the causal effect of this one-off windfall on all municipal accounting positions. We show that it triggered large expenditure increases targeting particular groups (e.g., salaries of public employees) at the same time as general tax cuts and user charge hikes (e.g., nursing home fees). The resulting imbalances caused a 7.5-fold increase in gross debt relative to the windfall. This massive overreaction hints at a substantial fiscal windfall curse.
Keywords: D70; H11; H71; H72; 330; local public finance; fiscal windfalls; fiscal policy